COMPLAINING STRATEGIES USED BY THE EFL LEARNERS OF ENGLISH STUDY PROGRAM IN RIAU - Sri Mahmudah; Indah Tri Purwanti; Rumiri Aruan (JURNAL PAJAR (Pendidikan dan Pengajaran), 2022)
Complaint commonly appears in daily life interaction (Sukyadi, 2011). People do not only provide words when they speak up but also deliver an action. The way how they complain is sometimes different. Hence, the study described in this article aimed to investigate the types of complaining strategies produced by the EFL learners of the English Study Program at Universitas Riau. The research was conducted in Pekanbaru. Research design used was a descriptive qualitative study accompanied by descriptive statistics. The participants of the research involved 36 EFL students of the English Study Program selected by using the cluster random sampling technique. The data were collected by using a DCT( Discourse Completion Task) system consisting of some situations in which students were requested to express their complaints. The result showed that the students mostly used direct complaint strategies. Subsequently, based on the overall strategies, the direct accusation strategy appeared as the strategy mostly employed by students in their daily interactions. It means that they prefered to give a direct and simple complaint by using a question to accuse the complainant directly. Moreover, they complain about something by using an Indonesian structural context as their L1, which was not appropriate in the English structural context as their L2. One of the strategies that were not used by the students was the direct strategy to condemn or curse the defendant’s actions because it was claimed as a harsh accusation.